Spatial Variability of Electrical Conductivity of Soils Irrigated with Brackish Water in the Arid Region of Rajasthan, India - Joshi, D C; Toth, Tibor; Sari, Diana (Annals of Arid Zone, 2016)
Saline and/or high residual sodium carbonate (RSC) ground water is the major source of irrigation in arid region of India. Despite fallowing during rainy season or amelioration with gypsum, high salinity prevails in the irrigated soils. There is a large spatial variability in the amount of accumulated salts. Present study was taken up to characterize the spatial variability in soil salinity at three sites on famlers’ fields where saline/high RSC (EC 3.6 to 8.6 dS m,l, SAR 19 to 62 and RSC I to 19 me L,I) is being used for irrigation for over ten years and some of the parcels have received gypsum for amelioration of sodicity. Salinity was measured at 5 m interval with a portable electrical conductivity meter SCT - I0 using four electrodes. The data were analyzed for basic statistical parameters and transformed into natural logarithm to provide a distribution closure to nomlal. For two sampling directions, the semi-variogram has been calculated. The results revealed that the nugget, sill and range of the semi-variogram seemed to depend on irrigation water salinity and soil texture. The largest range (70 m) was found at Narwa where the salinity of irrigation water was less and soil was loamy sand. At Sathin-l and Sathin-2 sites low range of 15 m and I I m, respectively, was attributed to fine texture and high sodicity of soil.